2013
DOI: 10.1124/jpet.113.207522
|View full text |Cite
|
Sign up to set email alerts
|

Stimulants as Specific Inducers of Dopamine-Independent σ Agonist Self-Administration in Rats

Abstract: A previous study showed that cocaine self-administration induced dopamine-independent reinforcing effects of s agonists mediated by their selective actions at s 1 receptors (s 1 Rs), which are intracellularly mobile chaperone proteins implicated in abuserelated effects of stimulants. The present study assessed whether the induction was specific to self-administration of cocaine. Rats were trained to self-administer the dopamine releaser dose-dependently blocked PRE-084 self-administration but was inactive agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…The goal was to have the food-reinforcement comparator procedurally and functionally as similar as possible to the drug self administration procedure. As shown previously with this procedure, the rates of foodreinforced responding were an inverted U-shaped function of food amount (Hiranita et al, 2013b;Li et al, 2013).…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The goal was to have the food-reinforcement comparator procedurally and functionally as similar as possible to the drug self administration procedure. As shown previously with this procedure, the rates of foodreinforced responding were an inverted U-shaped function of food amount (Hiranita et al, 2013b;Li et al, 2013).…”
Section: Methodssupporting
confidence: 75%
“…Although evidence supports the selectivity of (1)-pentazocine (Hellewell et al, 1994;Hiranita et al, 2013b), as well as PRE-084 [2-(4-morpholinethyl) 1-phenylcyclohexanecarboxylate hydrochloride] (Garcés-Ramírez et al, 2011), for s 1 Rs, there are few identified s 2 R-selective ligands (Matsumoto, 2007). Moreover, identification of in vivo functional agonists and antagonists at either sR subtype has historically been problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps related, ketamine is a powerful mobilizer of midbrain catecholamines, particularly dopamine, and these properties could account for both the psychotomimetic and antidepressant properties (Tan et al, 2012). However, a recent rat study indicated that although self-administration of d-amphetamine reinforces sigma 1 receptor agonist use that can be blocked by dopamine antagonists, similar effects on sigma agonist use are not observed for ketamine (Hiranita et al, 2013). These data suggest that ketamine's antidepressant effects are independent of dopaminergic/sigma 1 interactions (Hiranita et al, 2013).…”
Section: Other Moa'smentioning
confidence: 99%
“…
I found that several N-substituted benztropine (BZT) analogs (JHW 007 and AHN 2-005) can dose-dependently decrease self-administration (SA) of stimulants cocaine (Coc) or dmethamphetamine (MA) despite their high affinity and high selectivity for the dopamine transporter (DAT) [1,2]. In addition, the sigma receptor (σR) antagonist rimcazole and its analogs (SH 3-24 and SH 3-28) dose-dependently decrease Coc SA [3].
…”
mentioning
confidence: 99%
“…respectively [1,4]. The discovery of the reinforcing effects of the σR agonists was unexpected because a number of the previous studies generally failed to observe substantial behavioral effects of the σR agonists [8].…”
mentioning
confidence: 99%